PENGARUH DER DAN NPM TERHADAP HARGA SAHAM DIMEDIASI OLEH KEBIJAKAN DIVIDEN: PENGARUH DER DAN NPM TERHADAP HARGA SAHAM DIMEDIASI OLEH KEBIJAKAN DIVIDEN (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2026)
This research aims to determine the effect of DER and NPM on stock prices with dividend policy as an intervening variable in textile sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2023. The sampling technique used was purposive sampling, which means that samples were selected based on specific criteria. The population in this research consisted of 21 companies, and the sample consisted of 9 companies with 6 years of observation, resulting in a total sample of 54. The analysis technique used was path analysis. The results of the sub-structure I test showed that the Debt to Equity Ratio affected dividend policy, while the Net Profit Margin did not affect dividend policy. The results of the sub-structure II test show that Net Profit Margin affects stock price, while Debt to Equity Ratio and dividend policy do not affect stock price. The Sobel test results show that dividend policy is unable to mediate the effect of Debt to Equity Ratio and Net Profit Margin on stock price. Keywords: Debt to Equity Ratio, Net Profit Margin, Dividend Policy, Stock Prices